Development of Anti-bodies against Infliximab in Iraqi Patients with Rheumatoid Arthritis. - Al-Karkhi, Mohammed A.; Al-Ani, Muhammed M.; Jassim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Rheumatoid arthritis is a common chronic and destructive autoimmune arthropathy .Treatment with infliximab gives great improvement to a large numbers of patients with RA ,however, in some patients after prolonged treatment infliximab can induce anti-infliximab antibodies formation and result to loss of infliximab efficacy and active persistent disease.Objective: to investigate the frequency of anti-infliximab antibodies in Iraqi patients with rheumatoid arthritis.Patients and methods: fifty Iraqi RA patients(36 females and 14 males) compared with 50 control( 25 healthy control and 25 case control (patients with RA on other treatment) ) were included in this study from begging of March 2014 till end of September 2014.All patients were diagnosed by full history, complete clinical examination and laboratory test. Anti-infliximab antibodies were meatured using enzymelinked immunosorbent assay in serum of Iraqi patients with RA treated with infliximab more than 3 monthsduration.Results: Antibodies to infliximab were detected in 35(70%) Iraqi RA patients , while the patients without detectable antibodies against infliximab were 15(30%),also there were no anti-infliximab antibodies in the control groups.Conclusion: In this study, nearly three quarter of the Iraqi RA patients treated with infliximab developed anti-infliximab antibodies.